Combined use of endosonography and endoscopic retrograde cholangiopancreatography in the same session - Belkıs Ünsal,; Emrah Alper,; Behlül BAYDAR,; Fatih Aslan,; Zehra Akpınar,; Zafer BUYRAÇ,; Mehmet Kadir AKSÖZ, (Turkish Journal of Gastroenterology, 2019)
-